Welcome from the Symposium President - Lewillie, L. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
It is indeed a pleasure to see all of you here at this Opening Session of the 2nd International Symposium on Biomechanics in Swimming. As Symposium President and Chairman of the Organizing Committee, I wish to extend to you a most sinc;ere welcome. Four years ago many of us met here for the first symposium. Our purpose then was to bring together persons interested in the biomechanical aspects of swimming so that better communication and exchange of ideas among scientists and practitioners would be possible. In so doing, we would complement the work undertaken through the International Seminars on Biomechanics. Your presence today indicates that interest generated during the first symposium continues to grow and develop.